2016
DOI: 10.1002/cssc.201601232
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Decarbonylation of Furfural to Furan Catalyzed by Zirconia‐Supported Palladium Clusters with Low Atomicity

Abstract: Decarbonylation of furfural to furan was efficiently catalyzed by ZrO -supported Pd clusters in the liquid phase under a N atmosphere without additives. Although Pd/C and Pd/Al O have frequently been used for decarbonylation, Pd/ZrO exhibited superior catalytic performance compared with these conventional catalysts. Transmission electron microscopy and X-ray absorption fine structure measurements revealed that the size of the Pd particles decreased with an increase in the specific surface area of ZrO . ZrO wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Although Al 2 O 3 -supported Pd displayed high catalytic activity, ap oor materialb alancew as caused by the generation of several dimer byproducts and other polymerizedc ompounds. The use of commercially availableP d/C and Pd(OH) 2 /C resulted in considerably worse yields (Table1,e ntries [11][12]. Therefore, the size of the Pd NPs that were deposited on the metal oxide and the nature of the support could greatlyi nfluence the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Al 2 O 3 -supported Pd displayed high catalytic activity, ap oor materialb alancew as caused by the generation of several dimer byproducts and other polymerizedc ompounds. The use of commercially availableP d/C and Pd(OH) 2 /C resulted in considerably worse yields (Table1,e ntries [11][12]. Therefore, the size of the Pd NPs that were deposited on the metal oxide and the nature of the support could greatlyi nfluence the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…[8a,f] Very recently,o ur group reported am ethodt od ecarbonylate furfural to furan catalyzed by aZ rO 2 -supported Pd catalyst withouta dditives. [12] In that work, the Pd/ZrO 2 catalytic activity was significantly affected by the Pd particle size. We have also Highly efficient Wacker oxidationofaromatic or aliphatic terminal alkenes into methyl ketones and benzofurans is developed by using reusable Pd 0 nanoparticles (NPs) supported on ZrO 2 under acid-and cocatalyst-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Supported palladium catalysts are readily separated and recycled through filtration or centrifugation. [14][15][16] Compared with other carriers [e.g.,s ilica, [17] zeolite, [18] metal oxides, [19,20] metalorganic frameworks (MOFs), [21] etc. [11][12][13] Previous studies have demonstrated that the interactions between catalytic speciesa nd the support play significant roles in the catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Pd(OH) 2 /ZrO 2 exhibited the highest activity and selectivity (entry 6). The homogeneous Pd catalysts Pd(OAc) 2 and Pd(OH) 2 showed much inferior catalytic activities to Pd(OH) 2 /ZrO 2 under our conditions due to the formation of Pd black (entries 8 and 9). This result suggested that ZrO 2 support ef ciently stabilized Pd(II) during the reaction.…”
Section: Intramolecular C H/c H Couplingmentioning
confidence: 88%